Trend of lung cancer surgery, hospital selection, and survival between 2005 and 2016 in South Korea. Issue 2 (20th November 2021) - Kim, Dohun; Kang, Gil‐Won; Jang, Hoyeon; Cho, Jun Yeun; Yang, Bumhee; Yang, Hee Chul; Hwang, Jinwook
Abstract: Background: Studies on the clinical implication of hospital selection for patients with lung cancer are few. Therefore, this study aimed to analyze 2005–2016 data from the Korean national database to assess annual trends of lung cancer surgery and clinical outcomes according to hospital selection. Methods: Data of 212 554 patients with lung cancer who underwent upfront surgery were screened. Trends according to sex, age, residence, and income were examined. Descriptive statistics were performed, and p trend values were estimated. The association between survival and hospital selection was assessed using the log‐rank test. A multivariate Cox regression analysis was also performed. Results: A total of 49 021 patients were included in this study. Surgery was prevalent among men, patients aged 61–75 years, capital area residents, and high‐income patients. However, with the increasing rate of surgery among women, patients aged ≥76 years, city residents, and middle‐income patients, the current distribution of lung cancer surgery could change. The rate of lobectomy among these groups increased. All patients, except those in capital areas, preferred a hospital outside their area of residence (HOR); the number of patients with this tendency also increased. However, this trend was not observed among low‐income patients and those aged ≥76 years. There were significant differences in survival according to hospital selection. Conclusions: The trend of lung cancer surgery is changing. The current medical system is effective in providing lobectomy for patients including women, aged ≥76 years, city residents, and middle‐income. Increasing tendency to choose an HOR requires further study. Abstract : The trend of lung cancer surgery is changing. Women, ≥76 years, city residents, and middle‐income increased. All patients, expect those in capital areas, preferred hospital outside their area of residence. The rate of lobectomy increased.